Perception of having children through surrogacy in individuals with MRKH in Vietnam: a qualitative study - Le, Thanh T. Q.; Le, Nhung T. H.; Vu, Tuan A.; Nguyen, Hoa H.; Vuong, Lan N. (Frontiers in Psychology, 2024)
Introduction Mayer-Rokitansky-Küster-Hauser syndrome (MRKH) is rare condition that has a negative impact on quality of life because affected women lack a uterus and vagina, and are therefore unable to engage in sexual intercourse and experience natural pregnancy. This study evaluated perceptions of surrogacy in Vietnamese women with MRKH who have started families. Method Women with MRKH who had undergone successful vaginal reconstruction, were married, and had started families participated in a semi-structured, in-depth, one-on-one online video interview with an experienced female psychologist. Open-ended questions were used to encourage participants to express their perceptions of surrogacy; prominent themes were discussed, compared, and combined. Results Twenty women (mean age 31 years) agreed to participate. Key themes identified from interviews were the importance of having genetic offspring, consideration of surrogacy as a preferred solution to infertility, the barriers to surrogacy in Vietnam, lack of reproductive information and counselling, individuals concealing their health condition, the impact of religion on the possibility of surrogacy, the economic cost of surrogacy, and the difficulty in finding a surrogate under the restrictions imposed by Vietnamese law. Discussion Based on the perceptions of women from MRKH from Vietnam, there is an opportunity to improve how infertility is managed in these people, including information about surrogacy. These data show that individuals with MRKH should be provided with information about the possibility of surrogacy, encouraged to be open and seek support, and be managed by a multidisciplinary team that includes psychological support; the provision of economic support for fertility treatments in women with MRKH should also be considered.